Economic sociology, the natural environment, and the intellectual division of labor - Caleb Scoville (economic sociology. perspectives and conversations, 2024)
Suddenly it appears that the natural environment is at the front of sociologists' minds.1 It's an exciting moment, but it's also a bit awkward. Environmental sociologists, alongside other environmental social scientists in adjacent disciplines and interdisciplinary fields, have been working on ecological crises and environmental inequalities for decades, but they have largely been relegated to the margins of sociology. How should economic sociologists navigate this complex intellectual landscape, in light of their track record of having little to say about nature, environmental issues, or climate change?
Keywords: 300